2013
DOI: 10.1177/1464420713499514
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and finite element analysis of mechanical and fracture behaviour of Al2O3 particulate-filled A356 alloy composites: Part II

Abstract: In the present work, alumina (Al 2 O 3 )-filled cast aluminium alloy (A356) composites were fabricated using stir casting technique by varying Al 2 O 3 contents (0, 5, 10, 15, 20 and 25 wt.%). The fabricated composites were studied for their physical, mechanical and fracture toughness behaviour experimentally, theoretically and compared with finite element analysis method to validate the experimental and theoretical results. The physical and mechanical results showed that the addition of alumina to A356 alloy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The reason for adding 2.5% reinforcement was to avoid porosity and distribute it uniformly in the matrix. Kukshal et al 28 reported that composite porosity increases in tandem with the volume fraction of the reinforcement. Even with this low percentage of reinforcement, strength was enhanced.…”
Section: Experimental Procedures Composite Fabricationmentioning
confidence: 99%
“…The reason for adding 2.5% reinforcement was to avoid porosity and distribute it uniformly in the matrix. Kukshal et al 28 reported that composite porosity increases in tandem with the volume fraction of the reinforcement. Even with this low percentage of reinforcement, strength was enhanced.…”
Section: Experimental Procedures Composite Fabricationmentioning
confidence: 99%